PARADOX IN ARUNDHATI ROYâS THE GOD OF SMALL THINGS - Simamora, Rosa Maria (MEDIA UNIKA - Majalah Ilmiah, 2013)
This writing discusses paradox in the novel The God of Small Things written by Arundhati Roy. Although the novel and the author are claimed to be controversial for her dare to break the rules, the novel was awarded The Booker Prize. Her way to break the rules is clearly shown through the use of paradox on almost every page. This is a library research and applies New Criticism proposed by M.H. Abrams. He states that the distinctive procedure of the New Criticism is its explication or close reading; detailed and subtle analyses of the complex interrelation and ambiguities (multiple meanings of the components within a work). It gives much attention to the language especially paradox, irony, complexity, contrast, tension, etc.. In this writing paradox is a person, situation, and action exhibiting inexplicable or contrary aspect. The discussion is limited on the use of paradox in events, characters, and language. The intention is shown through the interpretation. Paradox in the events is traced through main and complementary events. It is found that paradox is used to criticize Syrian Christians who force on breeding marriage and curse inter-religion and inter-clan marriages. It is also used to portray the abuse of people right and dignity. Paradox in characters is traced through major and minor characters. It is found that Paradox is used to show people who claim and be claimed to be respected are in fact savage, but the discarded people have humanity values and capabilities. Paradox in language is traced through phrases of sentences. In conclusion, the novel the God of Small Things is enriched on Paradox. Arundhati Roy intentionally and beautifully used it to criticize and blaspheme the Syrian Christian teachings which stresses and forces on marriage within the same caste where the innocent people become the victims of the teaching.